Liquefaction Potential Evaluation by Deterministic and Probabilistic Approaches - Md Belal Hossain; Md Roknuzzaman; Md Mahabub Rahman (Salehan Institute of Higher Education, 2022)
Bangladesh is one of the world's most disaster-prone areas. The northwest region of Bangladesh is the most seismically active region. Dinajpur is the district closest to the Himalayan frontal thrust, making it the most vulnerable to earthquake-related liquefaction. Therefore, the in-situ parameters are used to assess the liquefaction susceptibility of the subsurface geology for the Dinajpur district in terms of soil liquefaction safety factor (FS), the liquefaction potential index (LPI), and the liquefaction probability (PL). This study used deterministic and probabilistic techniques to estimate the liquefaction susceptibility of the area based on standard penetration test (SPT) N values. SPT data was collected at 160 different places within the study area. In an earthquake scenario with Mw = 6.5, liquefaction resistance is evaluated at each location using a 0.20g peak ground acceleration (PGA). The results of the SPT-based liquefaction assessment techniques were found to be considerably different. The soil strata prone to liquefaction in different zones of the city have been determined based on a common comparison. According to deterministic and probabilistic techniques, it has been found that, out of 160 locations, 36 and 50 sites are susceptible to liquefaction. Then, using geospatial techniques (IDW interpolation), hazard maps were created depending on the potential for liquefaction of particular locations. Finally, using an independent secondary dataset, the resulting hazard maps were validated to examine the developed approach. The obtained R2values for each regression analysis event were more than 0.79. Therefore, the produced hazard map may be utilized successfully for planning, management, and long-term development of the studied locations. Doi: 10.28991/CEJ-2022-08-07-010 Full Text: PDF